EXPLORING PERSONALITY DEVELOPMENT AMONG TEACHER TRAINEES: A STUDY BASED ON THE BIG FIVE PERSONALITY TRAITS - Dr. Poonam Bhimrao Waghmare, Dr. Kavita Maruti Ghughuskar (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Personality development plays a crucial role in shaping effective educators, particularly during the formative period of teacher training. This study investigates the personality development of teacher trainees by focusing on the Big Five personality traits—extraversion, agreeableness, conscientiousness, neuroticism, and openness to experience. These traits are widely recognized as fundamental dimensions of human personality, influencing an individual’s behaviour, interpersonal relationships, and professional effectiveness. The research employs a survey-based methodology, gathering data from a diverse sample of teacher trainees at various stages of their training program. By utilizing validated instruments to measure each Big Five trait, the study examines how these traits are expressed among teacher trainees. It tracks any changes or developments throughout their training. The aim is to identify patterns and trends that can inform how these traits are nurtured during the critical period of teacher education. The findings of this study have significant implications for teacher training programs. They provide insights into which personality traits are most prevalent or underdeveloped among trainees, suggesting areas where targeted interventions could be beneficial. For example, enhancing traits like conscientiousness and agreeableness might improve classroom management and student engagement, while fostering openness to experience could encourage innovative teaching practices. Conversely, understanding the impact of neuroticism can help in developing support systems to manage stress and emotional challenges that teacher trainees may face. Ultimately, this research contributes to a deeper understanding of the role personality development plays in preparing future educators. By identifying key personality traits that can be cultivated during training, this study offers practical recommendations for teacher education programs aiming to produce well-rounded, effective teachers who are equipped to meet the diverse needs of their students.